Optimizing treatment strategies for pediatric phimosis and redundant prepuce: a comparative study of traditional circumcision and disposable circumcision stapler - Zhang, Guoyan; Luo, Yongliang; Cheng, Shangchao; Tu, Yonglang; Meng, Xiangyu; Wu, Linde; Li, Gang; Chen, Xiyuan (Frontiers in Pediatrics, 2024)
Objective: To investigate the surgical outcomes and complication rates of traditional circumcision and disposable circumcision stapler in the treatment of pediatric patients with phimosis and redundant prepuce. Methods: A retrospective analysis was conducted on pediatric patients with phimosis or preputial redundancy treated at our pediatric surgery department from January 2022 to December 2023. The patients were divided into two groups: treated with traditional circumcision (control group) and treated with a disposable circumcision stapler (experimental group). Surgical parameters (operation time, intraoperative bleeding), postoperative outcomes (postoperative pain scores, wound healing time, severe edge swelling, wound dehiscence, postoperative rebleeding, postoperative infection, aesthetic satisfaction), were compared between the two groups. Results: A total of 301 pediatric patients were included in our study, with 146 in the traditional group and 155 in the stapler group. The stapler group showed significantly lower values in operation time, intraoperative bleeding, and postoperative rebleeding compared to the traditional group (P＜0.05). However, the traditional group had a significant advantage in postoperative wound healing time and the occurrence of severe edge swelling (P＜0.05). There were no significant differences between the two groups in terms of anesthetic drug dosage, postoperative pain level, postoperative infection rate, wound dehiscence, and aesthetic satisfaction (P＞0.05). Conclusion: In the treatment of pediatric phimosis and redundant prepuce, the advantage of traditional circumcision lies in faster postoperative recovery and less severe edge swelling. The disposable circumcision stapler excels in thorough hemostasis, easy and safe operation, suitable for primary medical use, but lags behind in postoperative recovery compared to the traditional method. Each treatment approach has its own advantages, and the choice should be based on the actual condition and circumstances of the patient. Personalized treatment decisions should be made collaboratively to achieve the best therapeutic outcomes.